Assessment of physicochemical properties of polysaccharide derived mucoadhesive hydrogels to design tunable drug delivery carriers - Ankita Kumari; Diwanshi Sharma; Baljit Singh (Medicine in Novel Technology and Devices)
Recent initiatives have focused on designing copolymeric materials from bioactive polysaccharides, unveiling new horizons for their transformative use in biomedical applications. Sterculia gum (SG) is a bioactive polysaccharide which exhibits various therapeutic activities and effective in wound healing. Herein this research SG derived hydrogels were designed for wound dressing (WD) and drug delivery (DD) applications. These hydrogels were prepared by integrating PVP and HEMA onto SG by crosslinking polymerization reaction and were encapsulated with doxycycline to enhance potential of WD for healing. Copolymeric films were characterized using various techniques such as FESEM, EDS, AFM, FTIR, 13C NMR, XRD and various biomedical assays. Uneven porous morphology along with rough surface of hydrogels was recognized from FESEM and AFM analysis. XRD demonstrated the amorphous state of materials. FTIR and 13C NMR confirmed integration of PVP and PHEMA onto SG. Hydrogel exhibited bioadhesive, biocompatible and antioxidant properties. Diffusion of doxycycline followed a non-Fickian mechanism of diffusion consistent with kinetic model Korsmeyer-Peppas. The dressings were elastic and demonstrated mechanical stability during evaluation of tensile strength. Additionally, dressing displayed antimicrobial activity against P. aeruginosa, E. coli, and S. aureus. The biomedical properties suggested that SG derived hydrogel could be utilized in applications for WD and drug delivery.